Intravitreal anti-vascular endothelial growth factor, laser photocoagulation, or combined therapy for diabetic macular edema: A systematic review and network meta-analysis - Chen, Jiasheng; Wang, Haowei; Qiu, Weiqiang (Frontiers in Endocrinology, 2023)
Purpose To conduct a network meta-analysis (NMA) comparing the efficacy of anti-vascular endothelial growth factor (VEGF) therapy alone versus laser photocoagulation (LP) therapy alone or anti-VEGF therapy combined with LP therapy for diabetic macular edema (DME). Methods PubMed, Embase, Web of Science, and Cochrane Central Register of Controlled Trials were systematically searched for studies comparing anti-VEGF therapy alone versus LP therapy alone or anti-VEGF therapy combined with LP therapy for DME. Primary outcomes were mean best-corrected visual acuity (BCVA) and central macular thickness (CMT) change. Relevant data were collected and pooled using NMA. Results A total of 13 randomized controlled trials were included in our NMA. Anti-VEGF therapy significantly improved BCVA the most compared to the combined (mean difference [MD] = 1.5; 95% confidence interval [CI]: 0.084, 2.7) and LP (MD = 6.3; 95% CI: 5.1, 7.6) therapies at six months, while there was no difference in reducing CMT at six months between the anti-VEGF and combined therapies (MD = -16; 95% CI: -46, 13). At 12 months, no significant difference was found between the anti-VEGF and combined therapy in terms of BCVA (MD = 0.1; 95% CI: -1.7, 1.5) and CMT (MD = 21; 95% CI: -3.0, 44). Conclusion There was no significant difference between the anti-VEGF therapy and combined therapy. For the long-term treatment of patients with DME, combined therapy is recommended. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022376401.